A Deciphering of a Wonderful Cipher: Eleven in the architecture of Carlo Scarpa - Marco Frascari (Oz, 1991)
The Beginning Trace: I am a 13. Anton Francesco Doni was an 18, Antonio Abbondi, called the Scarpagnino, was a 14, called the 11.